1997
DOI: 10.1046/j.1365-2133.1997.17651853.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of the Ca2+ binding S100 proteins in normal human skin and melanocytic lesions

Abstract: The purpose of this study was to evaluate the expression of the Ca(2+)-binding S100 proteins S100A1, S100A2, S100A3, S100A4, S100A6 and S100B in normal skin. These immunohistochemical staining patterns were compared with those in melanocytic lesions. Paraffin-embedded tissue of normal skin adjacent to 26 naevi, 39 primary cutaneous melanomas and 14 cutaneous melanoma metastases was incubated with polyclonal antibodies against the recombinant human S100 proteins (S100A1, S100A2, S100A3, S100A4, S100A6, S100B) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
92
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 14 publications
4
92
0
1
Order By: Relevance
“…27 Recent investigations have emphasized the potential diagnostic and oncogenetic role of S100 proteins in a variety of tumors. [28][29][30][31][32][33][34] In this study, we found that S100A1 protein is expressed in renal oncocytomas, and in clear cell and papillary renal cell carcinomas but not in chromophobe renal cell carcinomas. We found significant statistical differences between S100A1 immunoexpression in clear cell and chromophobe renal cell carcinomas (Po0.001), which suggests that S100A1 could be a useful tool in their differential diagnosis.…”
Section: Discussionmentioning
confidence: 73%
“…27 Recent investigations have emphasized the potential diagnostic and oncogenetic role of S100 proteins in a variety of tumors. [28][29][30][31][32][33][34] In this study, we found that S100A1 protein is expressed in renal oncocytomas, and in clear cell and papillary renal cell carcinomas but not in chromophobe renal cell carcinomas. We found significant statistical differences between S100A1 immunoexpression in clear cell and chromophobe renal cell carcinomas (Po0.001), which suggests that S100A1 could be a useful tool in their differential diagnosis.…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have indicated that S100 proteins, due to their Ca 2 þ -binding properties, are involved in regulating intracellular Ca 2 þ homeostasis or Ca 2 þ -dependent cell signalling (Boni et al, 1997;Duarte et al, 1998). In addition, an intracellular relocation of S100A4 upon treatment with thapsigargin has been reported (Mueller et al, 1999).…”
Section: Discussion Transcriptional Regulation Of S100a4mentioning
confidence: 99%
“…In cardiomyocytes, AHNAK associates with the ␤ -subunit of cardiac L-type calcium channels and is phosphorylated by PKA in response to adrenoreceptor stimulation (Haase et al 1999). Moreover, we have shown that AHNAK interacts with the EF-hand calcium and zinc binding S100B protein (Gentil et al 2001), which is abundantly expressed in the central nervous system, skin, and muscle (Boni et al 1997;Shrestha et al 1998). Although studies on the cellular and sub-cellular localization of AHNAK in cultured cell lines are available in the literature, its tissue localization has been poorly investigated.…”
mentioning
confidence: 99%